Alteração de prazo dos contratos de concessão de serviços públicos como forma de recomposição de seu equilíbrio econômico-financeiro - Senna, Laís Ribeiro de (2018)
The purpose of this study is to analyze the public services concession agreement and the extension of its terms as a way to restore such economic and financial balance – guaranteed by the 1988 Brazilian Constitution – as defined by the contracting parties upon execution of the agreement. It also shows that the absence of any legal definition leaves much room for interpretation by the Public Administration, the regulatory agencies, and even the concessionaire, and this may result in the lack of legal uncertainty for concession agreements. In Brazil, the term extension has been widely used, despite the lack of any definition in the Constitution or federal laws. Furthermore, the rules and contracts that deal with such concept define renewal as any increase in the contract term, regardless of its nature. This may cause the term extension to be wrongly interpreted and applied, because such interpretation and application will be based on the conditions and consequences of another concept – the contract renewal, which is a prerogative of the Government taking into account the public interest. The two concepts, however, have different natures and, therefore, cannot be treated as equal. In addition, the lack of any legislation on the matter may raise certain doubts over the subject. Doubts as to whether there must be contractual provision, whether or not the two concepts can be applied concurrently, and what should be the limits to such application are some examples. The major concern, however, is whether the so-called extension is constitutional, given that the Brazilian Constitution determines that public service concessions must necessarily be preceded by a bidding procedure. Therefore, the scope of this study is to analyze not only the constitutionality of the term extension, but also its main features, conditions of interpretation and application, as well as to identify the problems that will have to be dealt with by legal scholars